Conflictul - atribut inerent al vieții sociale. Delimitări conceptuale [Articol] - Putină, Natalia (My University, 2019)
The history from ancient times to the present has demonstrated the inherent conflict in inter - human relations. Conflicts are a result of the interaction and communication of individuals, so they persist as long as man is. At present, conflicts are greatly influenced both by the nature of the people and by the specific nature of the work of social - political organizations and institutions. The i s- sue of conflicting conflicts and situations has become a key issue for many philosophers, psychologists, sociologists, political scientists, etc. But regardless of the high interest and long history there is no unanimously accepted understanding of the essence and nature of the conflict. The political sphere is a specific area that has a permanent and obviously conflictual character compared to other spheres of social life. Its origin is in the very nature of political relations, as relations of power, which presuppose the leadership of some and the subordination of others. That is, the power relations are based on the dominance of some people and their interests over others, which gives birth to clashes and confrontations. Political conflicts are a consequence of confrontations in a complex and multi-level system of leadership and subordination. This article will determine the conceptual, functional and structural dimension of conflicts, in particular will analyze the multitude of theories that enplane the expression of the conflicts in social and political life, constructive and negative approaches on functions of conflicts, dynamical dimension and particularities of political conflict management.
Keywords: conflict; cooperare; conflicte constructive și disctructive; soluționarea; rezolvarea conflictelor